Breaking frontiers with multidisciplinary cancer research - Caldas, Carlos; Chen, Xiaoyuan; Ding, Li; Kather, Jakob Nikolas; Scaltriti, Maurizio (Nature cancer, 2025)
Five experts share their thoughts on key areas of focus in multidisciplinary cancer research for the upcoming years. They discuss the research approaches, tools, technologies, collaborations and way of thinking the lab of the future should integrate.